Supervisory Communication Connection with Job Satisfaction In Fourth Industrial Revolution - Magdalena GĘBCZYŃSKA (Communications of International Proceedings, 2021)
Industry 4.0 is a combination of several cutting-edge technological developments, including but not limited to: Information and Communication Technologies, Cyber-Physical Systems, Network Communications, Big Data and Cloud Computing, Virtualization and Simulation and improved tools for human-computer collaboration. Digitalization will lead to the transformation of many organizational processes, such as: logistics, production, communication and human resources management. Every change makes it necessary for leaders whose task is to manage permanent change to use a range of skills for efficient implementation of these changes. One of the obstacles in this process is undoubtedly the resistance of employees, often resulting from lack of job satisfaction.  Employees job satisfaction in small and medium-sized manufacturing companies, especially in the process of digital transformation, is an empirically underexplored element. The aim of this paper is to examine the relationship between one of the leadership skills, i.e. supervisory communication and job satisfaction in small and medium-sized manufacturing companies operating under the conditions of Industry 4.0. A fuzzy/set qualitative comparative analysis was applied. The results of empirical research indicate that two constellations of dimension of supervisory communication lead to high job satisfaction. The first combines positive relationship communication, upward openness communication with absence of negative relationship communication. The second one combines positive relationship communication and job - relevant communication.
Keywords: supervisor; communication; job satisfaction; Industry 4.0; QCA